Chasing the high: the influence of addiction and personality on aggressive sexual behaviours - Schell, Rhianna (2018)
Perpetration of aggressive and violent sexual behaviours may be a sign of behavioural addiction. Previous research has suggested that frequent users of pornography also experience signs of behavioral addiction such as loss of control over use and preoccupancy with thoughts of using. Research has also suggested that frequent users experiencing signs of behavioural addiction are more likely to copy or fantasize about imitating what the see in pornography. However, most research has shown that only individuals experiencing psychopathic personality traits are the ones who will imitate what they see in pornography. A study of 1,060 persons explored the effects of addiction to pornography, the dark triad and personality, and addiction to sex as contributing factors to the perpetration of aggressive or violent sexual behaviours. Persons with higher scores of psychopathy and problematic pornography use and compulsive sexual behaviours were more likely to behave aggressively sexually, but the findings also indicate that, regardless of personality, individuals experiencing lower levels of sexual satisfaction also reported more sexual aggression.